In vitro enamel remineralization capacity of composite resins containing sodium trimetaphosphate and fluoride - Tiveron, Adelisa Rodolfo Ferreira [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Gaban, Gabriel [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Pedrini, Denise [UNESP] (Springer, 2015)
This study evaluated the in vitro enamel remineralization capacity of experimental composite resins containing sodium trimetaphosphate (TMP) combined or not with fluoride (F). Bovine enamel slabs were selected upon analysis of initial surface hardness (SH1) and after induction of artificial carious lesions (SH2). Experimental resins were as follows: resin C (control-no sodium fluoride (NaF) or TMP), resin F (with 1.6 % NaF), resin TMP (with 14.1 % TMP), and resin TMP/F (with NaF and TMP). Resin samples were made and attached to enamel slabs (n = 12 slabs per material). Those specimens (resin/enamel slab) were subjected to pH cycling to promote remineralization, and then final surface hardness (SH3) was measured to calculate the percentage of surface hardness recovery (%SH). The integrated recovery of subsurface hardness (ΔKHN) and F concentration in enamel were also determined. Data was analyzed by ANOVA and Student-Newman-Keuls test (p < 0.05). Resins F and TMP/F showed similar SH3 values (p = 0.478) and %SH (p = 0.336) and differed significantly from the other resins (p < 0.001). Considering ΔKHN values, resin TMP/F presented the lowest area of lesion (p < 0.001). The presence of F on enamel was different among the fluoridated resins (p = 0.042), but higher than in the other resins (p < 0.001). The addition of TMP to a fluoridated composite resin enhanced its capacity for remineralization of enamel in vitro. The combination of two agents with action on enamel favored remineralization, suggesting that composite resins containing sodium trimetaphosphate and fluoride could be indicated for clinical procedures in situations with higher cariogenic challenges.
Keywords: Composite resins; Phosphates; Sodium fluoride; Tooth remineralization